2023
DOI: 10.3390/jcm12134353
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Non-Responders Based on Quadriceps Force after Pulmonary Rehabilitation in COPD

Abstract: Pulmonary rehabilitation (PR) in patients with COPD improves quality of life, dyspnea, and exercise tolerance. However, 30 to 50% of patients are “non-responders” (NRs) according to considered variables. Surprisingly, peripheral muscle force is never taken into account to attest the efficacy of PR, despite its major importance. Thus, we aimed to estimate the prevalence of force in NRs, their characteristics, and predictors of non-response. In total, 62 COPD patients were included in this retrospective study (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…However, at the individual level, upon initiation of the program, the majority of the symptomatic patients had significantly increased muscle strength, as 53% exhibited an increase greater than the MCID. This prevalence of patient responses regarding muscle strength (i.e., 53%) is consistent with the study by Desachy et al, who reported a 50% response rate to QMVC at the end of a PR program in patients with chronic obstructive pulmonary disease [83]. The heterogeneity of responses to muscle strength is an important issue of current PR programs, as seen here for long COVID patients, and it highlights the importance of analyzing individual responses to conclude regarding PR (in)effectiveness and to consider care tailored to each patient.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, at the individual level, upon initiation of the program, the majority of the symptomatic patients had significantly increased muscle strength, as 53% exhibited an increase greater than the MCID. This prevalence of patient responses regarding muscle strength (i.e., 53%) is consistent with the study by Desachy et al, who reported a 50% response rate to QMVC at the end of a PR program in patients with chronic obstructive pulmonary disease [83]. The heterogeneity of responses to muscle strength is an important issue of current PR programs, as seen here for long COVID patients, and it highlights the importance of analyzing individual responses to conclude regarding PR (in)effectiveness and to consider care tailored to each patient.…”
Section: Discussionsupporting
confidence: 91%
“…This issue has been described, and a specific questionnaire, such as the DePaul Symptom Questionnaire-Post-Exertional Malaise, should be used to assess the prevalence of this symptom [82]. Concerning the relatively high prevalence of respiratory symptoms [23,82,83], this may be linked to an orientation bias of patients by prescribers. Indeed, the program was carried out in a center recognized nationally for its expertise in the management of chronic respiratory diseases, and thus, it is likely that long COVID patients with a high prevalence of respiratory disorders were preferentially referred to this center.…”
Section: Discussionmentioning
confidence: 99%